The Influence of Green Marketing and Green Products on The Decision to Purchase Bottled Drinking Water With Brand Image as a Mediating Variable - Admarianti, Ghina; Puspitaloka Mahadewi, Erlina (International Journal of Science, Technology & Management, 2026)
The purpose of this study was to determine the influence of green marketing and green products on purchasing decisions for bottled drinking water. This study used a quantitative survey method. The sample size was 160 respondents, who were bottled drinking water consumers living in Jakarta Indonesia. The sampling technique used was random sampling. Based on the results of the study, it can be concluded that green marketing and green products have a positive and significant influence on purchasing decisions. Furthermore, green marketing and green products have a positive influence on brand image. Based on the results of the study, it can be concluded that brand image has a significant influence on purchasing decisions. Furthermore, brand image can mediate the influence between green marketing and purchasing decisions, and brand image can also mediate the influence between green products and purchasing decisions. Based on the results of the study, it can be concluded that green products play a very important role in shaping brand image. Brand image was shown to have a positive and significant influence on purchase decisions, indicating that a positive brand image can increase consumer confidence in making purchasing decisions. The results of the mediation test indicate that brand image can mediate the influence of green marketing and green products on purchase decisions.